The Origin and Functions of Exosomes in Cancer - Rajagopal, Chitra; Harikumar, K. B. (Frontiers in Oncology, 2018)
Exosomes are nanovesicles having a maximum size of 150nm and is a newly emerging focus in various fields of research. Its role in cargo trafficking along with its differential expression is associated with the disrupted homeostasis and provides an opportunity to defend against different diseases like cancer. Furthermore, exosomes are rich in cargos which contain proteins and nucleic acids that directly reflect the metabolic state of the cells from which it originates. This review summarizes recent studies on tumor derived exosomes with an overview about biogenesis, their functions and potential of using as diagnostic and prognostic markers. We also discuss current challenges and microfluidic based detection approaches that might improve the detection of exosomes in different settings. More intricate studies of the molecular mechanisms in angiogenesis, pre-metastatic niche formation and metastasis can give more promising insights and novel strategies in oncotherapeutics.